Digitization of sunspot drawings by Spörer made in 1861–1894. Issue 1 (February 2015) - Diercke, A.; Arlt, R.; Denker, C.
Abstract Most of our knowledge about the Sun's activity cycle arises from sunspot observations over the last centuries since telescopes have been used for astronomy. The German astronomer Gustav Spörer observed almost daily the Sun from 1861 until the beginning of 1894 and assembled a 33‐year collection of sunspot data covering a total of 445 solar rotation periods. These sunspot drawings were carefully placed on an equidistant grid of heliographic longitude and latitude for each rotation period, which were then copied to copper plates for a lithographic reproduction of the drawings in astronomical journals. In this article, we describe in detail the process of capturing these data as digital images, correcting for various effects of the aging print materials, and preparing the data for contemporary scientific analysis based on advanced image processing techniques. With the processed data we create a butterfly diagram aggregating sunspot areas, and we present methods to measure the size of sunspots (umbra and penumbra) and to determine tilt angles of active regions. A probability density function of the sunspot area is computed, which conforms to contemporary data after rescaling. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)